Effects of drought and combined drought and heat stress on germination ability and seminal root growth of wheat (Triticum aestivum L) seedlings - Fábián, Attila; Jäger, Katalin; Barnabás, Beáta (Acta Biologica Szegediensis, 2008)
Wheat plants of the drought tolerant Plainsman V and sensitive Cappelle Desprez genotypes were subjected to drought and combined drought and elevated, 34/24 ºC day/night temperature at three various phases of reproductive development, at meiosis, from the 1st to the 5th day after pollination and from the 5th to the 9th day of seed development. After seed maturation, the germination frequency of the grains was calculated and the seminal root number of the seedlings was determined. Neither of the stress treatments affected the germination percentage of the genotypes significantly. Neither of the treatments reduced the number of seminal roots in the case of the tolerant genotype. However in sensitive variety the ratio of seedlings with only one root increased to 42% after drought stress, applied during the 5.-9. days after pollination. In this genotype the combined stress increased the proportion of one-rooted seedlings to 56% and 78% when applied during 1.-5. DAP and 5.-9. DAP, respectively. Histological studies revealed that the lateral root meristems were present in control and stressed embryos of both genotypes.